TCAM/CAM-QCA: (Ternary) Content Addressable Memory using Quantum-dot Cellular Automata. Issue 7 (July 2015) - Sardinha, Luiz H.B.; Silva, Douglas S.; Vieira, Marcos A.M.; Vieira, Luiz F.M.; Vilela Neto, Omar P.
Abstract This paper describes a Content Addressable Memory (CAM) architecture and its ternary variant called Ternary Content Addressable Memory (TCAM) using the Quantum-dot Cellular Automata (QCA). QCA is an alternative to the current integrated circuit (CMOS) paradigm based on the characteristics of confinement and mutual repulsion between electrons. It is expected to run with clocks in high frequency (in THz order), in nanometers scale and with very low energy consumption. First, this work presents the basic building blocks (1-bit memory cell, array of memory cells, ternary memory line and encoder). Then, we describe the complete TCAM and CAM architectures. Finally, the proposed architectures are tested and validated using QCADesigner simulator, attesting their functionalities. If QCA consolidates as a possible CMOS substitute, this study can impact the design of future components that uses TCAM and CAM such as routers and switches respectively.